Prediction of pedicled flap survival preoperatively by operating indocyanine green angiography at 1,450 nm wavelength: an animal model study - Shi, Chenchen; Guo, Linxiumei; Song, Ruihu; Xu, Heng; Zhang, Yixin (Frontiers in Medicine, 2024)
Background Predicting flap viability benefits patients by reducing complications and guides flap design by reducing donor areas. Due to varying anatomy, obtaining individual vascular information preoperatively is fundamental for designing safe flaps. Although indocyanine green angiography (ICGA) is a conventional tool in intraoperative assessment and postoperative monitoring, it is rare in preoperative prediction. Methods ICGA was performed on 20 male BALB/c mice under five wavelengths (900/1,000/1,100, /1,250/1,450 nm) to assess vascular resolution after ICG perfusion. A “mirrored-L” flap model with three angiosomes was established on another 20 male BALB/c mice, randomly divided into two equal groups. In Group A, a midline between angiosomes II and III was used as a border. In Group B, the points of the minimized choke vessel caliber marked according to the ICG signal at 1,450 nm wavelength (ICG1450) were connected. Necrotic area calculations, pathohistological testing, and statistical analysis were performed. Results The vascular structure was clearly observed at 1,450 nm wavelength, while the 900 to 1,100 nm failed to depict vessel morphology. Necrosis was beyond the borderline in 60% of Group A. Conversely, 100% of Group B had necrosis distal to the borderline. The number of choke vessels between angiosomes II and III was positively correlated with the necrotic area (%). The pathohistological findings supported the gross observation and analysis. Conclusion ICG1450 can delineate the vessel structure in vivo and predict the viability of pedicled skin flaps using the choke vessel as the border between angiosomes.